If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(-3) = -1 Multiply 3 * -3 2x + -9 = -1 Reorder the terms: -9 + 2x = -1 Solving -9 + 2x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2x = -1 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = -1 + 9 2x = -1 + 9 Combine like terms: -1 + 9 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 4x^2-24x+18=0 | | -x+13=4 | | 4x+12=-7 | | 3g=-9+2g | | 3.50=5.25-11 | | 13x+(1-x)(15)=13 | | y=5(x-6)(x+9) | | 10-(8-8n)+8n=-4+12(n+1) | | 5m+m^2= | | 5m+m^2=6m | | 3.50+11=5.25+11 | | 18y+24x= | | 0=-16t^2+144t+0 | | 75x+7=4 | | -15=0.2b | | G(5)=10x-4 | | 29-4(4-x)=1 | | -66=6.6v | | 10z^6+9z^3-9=0 | | 7x-2=5.5 | | 16k^2-52k+30= | | 5x+3y=1500 | | 6x-7=4x+2 | | B-23=33 | | 30.6=5.1k | | 2x-21=x-10 | | 24-3(4-x)=-6 | | 14x-17x=6 | | 6b-4+b=-12 | | 9r-4(r+2)=5(2r-4)-18 | | y=3(x+1)(x-7) | | -13=2.8+a |